2010
DOI: 10.1111/j.1365-2303.2010.00812.x
|View full text |Cite
|
Sign up to set email alerts
|

KRAS and BRAF mutation analysis can be reliably performed on aspirated cytological specimens of metastatic colorectal carcinoma

Abstract: A range of cytological samples are suitable for KRAS and BRAF mutation testing, be it from previously stained preparations or cell blocks. These samples would be highly valuable in cases where cytological samples are the only material available for mutation testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 29 publications
1
21
0
Order By: Relevance
“…The PCR amplification and subsequent direct sanger sequencing of BRAF exon 15 were carried out according to published protocols [11]. Our test validation of the BRAF exon 15 detection by direct sequencing had shown 100% sensitivity and specificity, with a lower limit of detection set to 30% of mutated cells in a background of 70% of non-mutated cells [12]. For KIT exons 9 and 11 mutation analysis, polymerase chain reaction (PCR) amplification of 100 ng of genomic DNA was set up as described previously [13].…”
Section: Methodsmentioning
confidence: 99%
“…The PCR amplification and subsequent direct sanger sequencing of BRAF exon 15 were carried out according to published protocols [11]. Our test validation of the BRAF exon 15 detection by direct sequencing had shown 100% sensitivity and specificity, with a lower limit of detection set to 30% of mutated cells in a background of 70% of non-mutated cells [12]. For KIT exons 9 and 11 mutation analysis, polymerase chain reaction (PCR) amplification of 100 ng of genomic DNA was set up as described previously [13].…”
Section: Methodsmentioning
confidence: 99%
“…(v-raf murine sarcoma viral oncogene B1) status with high concordance to primary lesions (17,19,(25)(26)(27). While conventional assays identify patients as RAS mutant when a mutation is detected in >10% of reads sequenced, sensitivities approaching 0.1% are now possible (28).…”
Section: Pik3camentioning
confidence: 99%
“…In this domain, neoplastic lesions of lymph nodes, soft tissue sarcomas, gastrointestinal stromal tumors and colon cancers have been studied, and some results have shown the use of cytological material for the management of patients with these malignancies [58,59,60,61,62,63]. …”
Section: Body Fluidsmentioning
confidence: 99%
“…However, there are some KRAS wild-type cases that are still unresponsive to anti- EGFR therapies. Some authors have shown that this unresponsiveness could be due to the presence of a discrepancy in KRAS status between the primary tumor and its metastases [62,63]. …”
Section: Primary Tumors and Metastasesmentioning
confidence: 99%